Analisis Efektivitas Dan Efisiensi Anggaran Belanja Operasional Tahun Anggaran 2019-2022 : (Studi Kasus Pada Dinas-Dinas Di Kota Bandung) - Raafi Melati Putri; Indri Yuliafitri (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The broad principles of autonomy in accordance with the principles of the Unitary State of the Republic of Indonesia grant the right to local regions to manage their own affairs, adapting policies to local characteristics and needs, thereby enhancing the effectiveness, efficiency, and accountability of governance at the local level. The management of local finances involves a series of actions carried out by financial management officials, including planning, implementation, monitoring, and accountability for these tasks. In the past five years (2019-2022), the City of Bandung government has analyzed the effectiveness and efficiency of the utilization of operational expenditure budgets by its departments. This budget is crucial in improving the quality of public services and meeting community needs, serving as a focal point for the evaluation of the city government's financial performance. The realization of Bandung City's operational budget from 2019 to 2022 indicates a fairly effective level of effectiveness (84%). Despite falling slightly below the target, the percentage of effectiveness increased from 81% (2019) to 87% (2022). In terms of efficiency, the city managed to save operational budget with a "very efficient" rating (15%), achieving efficiency percentages ranging from 12% to 23% during this period.